Membentuk Kurva Penawaran Berdasarkan Maksimisasi Profit - Munrokhim Misanam (Economic Journal of Emerging Markets, 2008)
Following the process of deriving demand curve, which traces it from the consumer behavior to keep being in the optimum utility, one should also be able to form supply curve from producer behavior especially in getting maximum profit. But this does not work. In the case of output maximization, instead of supply curve, one will ends up with demand for inputs. While when using profit-maximum condition, MC = MR, one will find an ambiguous situation. This is so because only segment that is above average cost, AC, represents maximum profit; while the other segment represents losses. However, this concept is not strong. Even in the segment that is perceived as representing maximum profit, there is also doubtful situation, as Misanam (2007) shows it, where there is no guarantee that the condition will surely produces the maximum profit; This happens because the failure to insert the second condition that serves as sufficient condition.This paper is trying to extend the finding of Misanam (2007): maximum profit condition. From the new profit maximization condition this article proceed further to explore the existence of the authentic supply curve. The exploration introduces a new concept which is called “marginal net advantage” that serves as the incentive for producer to produce more. Based on the new concept, the exploration finds production choice curve that is a locus for maximum profit. Finally, the authentic supply curve is formed by selecting  the most viable production choice curve. The resulted supply curve has actually a convex curve in nature, instead of linear line.*****Key words: Marginal net advantage, production choice curve